Ryan Howerter: capstone - Howerter, Ryan, artist (Colorado State University. Libraries, 2016)
The artist's statement: I am fascinated by the geometry and mathematics that compose everything, from the natural to the human-made. My art explores the beauty of pure form and pattern, calculated and precise. I believe that even minimalistic and decorative arts are inherently full of meaning and connotations, by virtue of the human hand that designed them. I most enjoy conceptual art, in which the idea of a previously-undiscovered art subject or methodology is worth exploring for its own sake. I appreciate the old Pennsylvania Dutch concept of "yuscht fer schnee" ("just for pretty"), in which artworks can be appreciated for their pleasing aesthetics alone, without the need to read deeper to find meaning. If unique patterns or skill in craft awe me, then I feel the art is already successful. There is no pretense of "elite" art or a hidden meaning, and to me this shows a certain humility. In my graphic design work, I aim for clarity and directness. To both catch the audience's eye and communicate information effectively and memorably is a balancing act. I obsess over minute adjustments and alignments-consistency is key. When nothing distracts from the design's intended message, then the design will be successful. This design philosophy extends to all of my art, whether it is digital, Lego, photography, or traditional media.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design